Biocatalytic Synthesis of D-Allulose Using Novel D-Tagatose 3-Epimerase From Christensenella minuta - Wang, Yang; Ravikumar, Yuvaraj; Zhang, Guoyan; Yun, Junhua; Zhang, Yufei; Parvez, Amreesh; Qi, Xianghui; Sun, Wenjing (Frontiers in Chemistry, 2020)
D-allulose, which is one of the important rare sugars, has gained significant attention in the food and pharmaceutical industries as a potential alternative to sucrose and fructose. Enzymes belonging to the D-tagatose 3-epimerase (DTEase) family can reversibly catalyze the epimerization of D-fructose at the C3 position and convert it into D-allulose by a good number of naturally occurring microorganisms. However, microbial synthesis of D-allulose is still at its immature stage in the industrial arena, mostly due to the preference of slightly acidic conditions for Izumoring reactions. Discovery of novel DTEases that works at acidic conditions are highly preferred for industrial applications. In this study, a novel DTEase, DTE-CM, capable of catalyzing D-fructose into D-allulose was identified and characterized from human intestinal gut bacterium, Christensenella minuta. The catalytic activity of dte on D-fructose was found to be remarkably influenced and modulated by the type of metal ions (co-factors). The addition of Ni2+ not only enhanced the enzyme activity, but also resulted in improving the enzyme half-life at 50℃ from 0.5 to 3.5 h at a concentration of 0.1 mM. The enzyme exhibited its maximum catalytic activity on D-fructose at pH 6.0 and 50 ℃ with a Kcat/Km value of 45 mM-1min-1. The enzymatic conversion of D-fructose into D-allulose using this enzyme produced 156 g/L D-allulose from 500 g/L D-fructose, which corresponded to 30 % conversion efficiency. With these interesting catalytic properties, the enzyme could be a promising candidate for industrial biocatalytic applications.